Rationality and religious commitment - Audi, Robert, 1941- (New York ; Oxford : Oxford University Press, 2011)
Can it be rational to be religious? Robert Audi gives a persuasive positive answer through an account of rationality and a rich, nuanced understanding of what religious commitment means. It is not just a matter of belief, but of emotions and attitudes such as faith and hope, of one's outlook on the world and of commitment to live in certain ways.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Faith and reason; Faith; Rationalism; Commitment (Psychology) -- Religious aspects; Religion and ethics